2019
DOI: 10.2323/jgam.2018.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Response surface optimization of conditions for culturing <i>Azotobacter chroococcum</i> in <i>Agaricus bisporus</i> industrial wastewater

Abstract: In the present study, the conditions for Azotobacter chroococcum fermentation using Agaricus bisporus wastewater as the culture medium were optimized. We analyzed the total number of living A. chroococcum in the fermentation broth, using multispectral imaging flow cytometry. Single-factor experiments were carried out, where a Plackett-Burman design was used to screen out three factors from the original six processing factors wastewater solubility, initial pH, inoculum size, liquid volume, culture temperature, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…The peak of the response surface could be used to analyze and forecast the results. 33 The linear coefficient (X 2 , X 3 ) and the quadratic term coefficient (X 3 2 ) exhibited a highly significant effect (P < 0.01), while the P-values of the interaction term coefficient (X 1 X 3 ) and the quadratic term coefficient (X 1 2) were all less than 0.05. These statistical results of the quadratic polynomial model indicated that the relationship between the variables and the response were not simply linear.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…The peak of the response surface could be used to analyze and forecast the results. 33 The linear coefficient (X 2 , X 3 ) and the quadratic term coefficient (X 3 2 ) exhibited a highly significant effect (P < 0.01), while the P-values of the interaction term coefficient (X 1 X 3 ) and the quadratic term coefficient (X 1 2) were all less than 0.05. These statistical results of the quadratic polynomial model indicated that the relationship between the variables and the response were not simply linear.…”
Section: Resultsmentioning
confidence: 95%
“…The Box−Behnken design was performed to study the individual and mutual interaction effects of the three selected parameters on PCA yields and determine the optimum level. 33 The BBD matrix and the results of PCA yield are presented in Table 1. After multiple regression analysis on the BBD data, the quadratic polynomial model was obtained, as given by eq 3…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations